2013
DOI: 10.1007/s11064-013-1160-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynactin Deficiency in the CNS of Humans with Sporadic ALS and Mice with Genetically Determined Motor Neuron Degeneration

Abstract: Dynactin is a complex motor protein involved in the retrograde axonal transport disturbances of which may lead to amyotrophic lateral sclerosis (ALS). Mice with hSOD1G93A mutation develop ALS-like symptoms and are used as a model for the disease studies. Similar symptoms demonstrate Cra1 mice, with Dync1h1 mutation. Dynactin heavy (DCTN1) and light (DCTN3) subunits were studied in the CNS of humans with sporadic ALS (SALS), mice with hSOD1G93A (SOD1/+), Dync1h1 (Cra1/+), and double (Cra1/SOD1) mutation at pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 49 publications
0
24
1
Order By: Relevance
“…The changes in dynactin DCTN1 expression in PBMCs of SALS patients were the opposite to those observed earlier in the brain cortex and the spinal cord [38]. In SALS brain motor cortex the expression of DCTN1 and DCTN3 mRNA was higher than in the sensory cortex.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…The changes in dynactin DCTN1 expression in PBMCs of SALS patients were the opposite to those observed earlier in the brain cortex and the spinal cord [38]. In SALS brain motor cortex the expression of DCTN1 and DCTN3 mRNA was higher than in the sensory cortex.…”
Section: Discussioncontrasting
confidence: 62%
“…Many papers indicated that disorders in the intracellular transport might be crucial for the initiation or progression of motor neuron degeneration [35,41,42,43,44]. In our previous studies, we observed important changes in the expression of tau isoforms, kinesins and dynactin in various regions of the CNS obtained from autopsies of SALS patients and transgenic mice with symptoms of motor neuron degeneration [36,37,38,45]. In the present work we investigated the expression of motor proteins in PBMCs obtained from a cohort of Polish SALS patients in comparison with healthy blood donors, and patients with other neurological diseases such as atypical parkinsonism and ALS-mimicking disorders.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations